Development-oriented foreign policy; a framework for analyzing Nordics relations - Reza Rahmati (رهیافتهای سیاسی و بین المللی)
Abstract Extended:Introduction: The establishment of a close relationship between sociology, political science and economics was established with the beginning of the new institutionalist debates in the mid-1980s and in particular with the efforts of Douglas North. Research findings show that this economic growth, increased foreign investment, trading partners (imports and exports), etc., is configured with attention to the internal environment. The Scandinavian economies (Denmark, Norway and Sweden) are among the richest economies in the world. Scandinavian people enjoy the highest living standards in the world due to a relatively low wage gap, very high employment and high taxes, along with good quality education and social security. From a regional perspective, Scandinavia is a cohesive region that performs much better than the average of the European Union and the Organization for Economic Cooperation and Development (OECD). However, these countries differ on a number of important parameters: Sweden has the largest economy, followed by Norway and Denmark. Norway, on the other hand, has the highest level of GDP per capita, while only Denmark has shown a positive GDP growth rate since the 2008 financial crisis. Accordingly, a look at the statistics and data on foreign trade, the total value of exports and imports, and the economic performance of these countries helps to a great extent to formulate development-oriented approaches based on institutional patterns, the embedding of the economy in politics, elite perception, and a development-oriented foreign policy. For example, statistics on exports and imports of goods and services in Scandinavia show that in the period 2010-2020, we see a significant growth in the total value of exports of these countries. Methods: The present research method will be developmental in terms of purpose, descriptive-analytical in terms of method, and library in terms of data collection. The author's approach will be descriptive and analytical.Results and Discussion: Classical approaches hold that foreign policy is separate from domestic policy and that states are like billiard balls on the international stage that are in a state of flux with respect to their domestic relations. This is while recent approaches hold that domestic policy and foreign policy have an inseparable relationship with each other. Institutionalism in political economy is one of the approaches that, while paying attention to social traditions and institutions, emphasizes the importance of domestic relations over foreign practices and approaches. This issue becomes more important when examined in the context of Scandinavian countries. The research hypothesis, while utilizing an anthology method and resorting to institutional, perceptual, and development-oriented approaches, is that foreign policy and domestic policy have intertwined and "etched" relationships with each other, in such a way that domestic policy, by offering cultural, political, economic, and social attractions, has been able to create an environment receptive to a dynamic economy, and foreign policy, with its mobility, has been able to advance the goals of developmentism by attracting foreign direct investment, national branding, international coordination, the greatest amount of international communications, neutrality, and de-securitization of economic relations. Institutionalism emerged in the late 1870s and in response to the mechanical rationalism of the classical and neoclassical schools of economics. Conclusion: Institutionalism gradually defined development from a non-classical perspective, given the major importance it gave to the cultural, social, political, and economic contexts and infrastructures of society. Institutions emerged as a product of human behavior and therefore were important. In the institutionalist model, political institutions are of great importance due to their importance in the formation, consistency and application of rules, both formal and informal, and therefore the role of the state in institutional economics becomes important.